Associations of Acrylamide Intake With Urinary Sex Hormone Levels Among Preschool-Age Japanese Children. Issue 1 (1st June 2017) - Nagata, Chisato; Konishi, Kie; Wada, Keiko; Tamura, Takashi; Goto, Yuko; Koda, Sachi; Mizuta, Fumi; Nishizawa, Sakiko; Sukigara, Etsuko; Watanabe, Kaori; Ando, Kyoko
Abstract: Acrylamide may affect the sex hormone system in the prepubertal period. This study examined the cross-sectional associations between dietary acrylamide intake and sex hormone levels among preschool-age Japanese children. The study was conducted in 2006 among 230 boys and 198 girls aged 3–6 years in Aichi, Japan. Acrylamide intake was assessed using 3-day diet records. Urinary concentrations of estrone, estradiol, testosterone, and androst-5-ene-3β, 17β diol (hereafter referred to as androstenediol) were measured by liquid chromatography–electrospray ionization–tandem mass spectrometry. Sex hormone levels were adjusted for urinary creatinine levels. The estimated acrylamide intake was 1.00 μg/kg of body weight per day. After controlling for age and other covariates, acrylamide intake was significantly positively associated with urinary levels of testosterone and androstenediol in boys. On average, boys in the highest quartile of acrylamide intake had 96.9% higher testosterone (95% confidence interval: −1.8, 295; P for trend = 0.048) and 34.5% higher androstenediol levels (95% confidence interval: −5.9, 92.3; P for trend = 0.04) than boys in the lowest quartile. In girls, there were no significant associations between acrylamide intake and the hormones measured. Acrylamide intake may alter androgen metabolism in preschool-age boys. Because this is a first observation, our findings require confirmation in additional studies.